A nap before retrieval reduces false identifications in target absent lineups - Bonilla, Matías (2025)
Eyewitness misidentifications are a major cause of wrongful convictions. While most research hasfocused on the role of sleep in memory encoding and consolidation, recent findings suggest thatnon-REM sleep may also enhance retrieval processes by restoring executive and monitoring functions.Here, we investigated whether a short nap before retrieval could improve performance in forensicmemory tasks. Participants watched an aversive video of a robbery and, after 24 h, either took a60-minute nap (Sleep group) or stayed awake (Wake group) before completing a series of memorytasks, including face recognition (target-present and target-absent lineups), free recall, contextrecognition, and temporal order. A nap prior to retrieval selectively reduced false identifications intarget-absent lineups, increasing correct rejections without affecting performance in target-presenttrials. Temporal order memory also improved in the Sleep group, whereas no significant differenceswere observed in free recall or context recognition. Confidence-accuracy calibration was strongerin the Sleep group, particularly when the perpetrator was absent. These findings suggest that abrief nap prior to memory retrieval may improve the accuracy of eyewitness decisions by enhancingmetacognitive monitoring and temporal discrimination, offering a simple, non-invasive intervention to reduce errors in forensic settings.